Satellite Analyses Unravel the Multi-Decadal Impact of Dam Management on Tropical Floodplain Vegetation - Salerno, Luca; Moreno-Martínez, Álvaro; Izquierdo-Verdiguier, Emma; Clinton, Nicholas; Siviglia, Annunziato; Camporeale, Carlo (Frontiers in Environmental Science, 2022)
An assessment of river regulation impact on floodplain vegetation is crucial to developing a modern watershed management approach in the Neotropics aimed at mitigating alterations of the floodplain environment. Nevertheless, floodplain forest monitoring requires high-resolution mapping, as vegetation dynamics are in the narrow area at the interface between terrestrial and aquatic systems. The existing satellite images that afford land observations have limitations due to coarse resolution or gaps in data caused by the extreme cloudiness of tropical regions. This study provides a new framework for high-resolution mapping and monitoring of a large-scale tropical forest in the aquatic-terrestrial zone (ATTZ) of an Amazon basin. The main aim is to assess the vegetation status and the environmental degradation in a highly altered fluvial setting. To achieve the goal, a remote sensing processing chain, which couples hydrologic and vegetation data, was developed. A map of high-resolution traditional vegetation indices and their non-linear generalization was derived from the high-resolution gap-free reflectance data obtained by combining Landsat and MODIS data, through the HISTARFM algorithm. Subsequently, hydrological modification within these areas was assessed by using a global water surface dataset. In addition, the impact of river regulation on riverine forest carbon cycling was assessed through the analysis of interannual variability of the gross primary production (GPP) of floodplain vegetation. The framework was applied to analyze the last two decades of changes in the floodplain forest of Uatuma river (central Amazon basin), downstream of the Balbina hydropower dam built in 1987. The analysis showed the presence of vegetation degradation in areas of increased hydrologic stress and upland forest encroachment in areas no longer inundated. The dam continues to have effects on vegetation even 30 years after its construction. The ongoing profound reshuffling of the floodplain forest, and the impact on the carbon storage capacity of the floodplain forest suggest that the situation is far from a new environmental equilibrium. The proposed high--resolution approach allows for a detailed mapping of riparian vegetation alterations, helping to develop a more careful management of the watershed through a better understanding of the human footprint on floodplain forests.